Cevaplar

2012-09-01T13:13:09+03:00

4,02 x 10^7 + 59,8 x 10^6  

 

10^7 yi 10 x 10^6 olarak yazabiliriz.

böylece 4,02 x 10^7 = 40,2 x 10^6 olur 

 

ifade şu an 40,2 x 10^6 + 59,8 x 10^6  haline geldi 

bu da  10^6 ( 40,2 + 59,8 ) demektir. 

 

yani  4,02 x 10^7 + 59,8 x 10^6     =  40,2 x 10^6 + 59,8 x 10^6

                                                   = 10^6  x ( 40,2 + 59,8 )

                                                   =  100 x 10^6

                                                   =  10^2 x 10^6

                                                   = 10^8

1 5 1
2012-09-01T15:33:45+03:00

 

4,02 x 10^7 + 59,8 x 10^6  

 

10^7 yi 10 x 10^6 olarak yazabiliriz.

böylece 4,02 x 10^7 = 40,2 x 10^6 olur 

 

ifade şu an 40,2 x 10^6 + 59,8 x 10^6  haline geldi 

bu da  10^6 ( 40,2 + 59,8 ) demektir. 

 

yani  4,02 x 10^7 + 59,8 x 10^6     =  40,2 x 10^6 + 59,8 x 10^6

                                                   = 10^6  x ( 40,2 + 59,8 )

                                                   =  100 x 10^6

                                                   =  10^2 x 10^6

                                                   = 10^8

 aynen böyle konu anlatımlı yok
0